1984
DOI: 10.1055/s-2007-1023335
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hemodynamics in Infants and Small Babies after Open Heart Surgery

Abstract: The study was undertaken to establish typical hemodynamic changes and reliable clinical tests for the evaluation of these in infants after open heart surgery. The cardiac index was measured using the thermodilution technique in 56 infants. The age of the patients varied from 6 to 28 months and body weight from 4 to 15 kg. All studies were done during the first 24 hours after operation. It was shown that in a hemodynamically smooth postoperative course cardiac index exceeds 2.7 l X min-1 X m-2, toe temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The use of thermal gradient as a tool for monitoring cardiac output is controversial. Older studies found an increase in thermal gradient correlated with an increase in systemic vascular resistance, a decrease in cardiac output, stroke index, and urine output (7,18,19). An increase in gradient preceded or was concomitant with changes in hemodynamic parameters (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of thermal gradient as a tool for monitoring cardiac output is controversial. Older studies found an increase in thermal gradient correlated with an increase in systemic vascular resistance, a decrease in cardiac output, stroke index, and urine output (7,18,19). An increase in gradient preceded or was concomitant with changes in hemodynamic parameters (18).…”
Section: Discussionmentioning
confidence: 99%
“…It was designed to predict adverse events potentially related to low cardiac output but has not been compared with an objective measure of cardiac output. Instead of toe temperature, several authors have proposed to use a thermal gradient between core and peripheral temperature with a threshold value of 5°C being correlated with decreased cardiac output and increased peripheral vascular resistance (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%